2014
DOI: 10.1155/2014/832161
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Carcinogenesis and the Mechanism Underlying by the Influence of Indole-3-carbinol and Its Metabolite 3,3′-Diindolylmethane: A Therapeutic Marvel

Abstract: Rising evidence provides credible support towards the potential role of bioactive products derived from cruciferous vegetables such as broccoli, cauliflower, kale, cabbage, brussels sprouts, turnips, kohlrabi, bok choy, and radishes. Many epidemiological studies point out that Brassica vegetable protects humans against cancer since they are rich sources of glucosinolates in addition to possessing a high content of flavonoids, vitamins, and mineral nutrients. Indole-3-carbinol (I3C) belongs to the class of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
8

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 52 publications
(88 reference statements)
2
44
0
8
Order By: Relevance
“…Moreover, our findings indicate that I3C may functions as a protector agent against AOM-induced DNA damage. To this regard, it is reported that I3C induces intestinal glutathione-S-transferase (GST), an enzyme involved in the detoxification of xenobiotics and in regulating antioxidant responses [32–34]. It is plausible, that I3C protective effect against DNA damage may be mediated by an increase in the detoxification of AOM, an alkylating agent that provokes DNA damage, resulting in antioxidant responses that confer protection within the colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our findings indicate that I3C may functions as a protector agent against AOM-induced DNA damage. To this regard, it is reported that I3C induces intestinal glutathione-S-transferase (GST), an enzyme involved in the detoxification of xenobiotics and in regulating antioxidant responses [32–34]. It is plausible, that I3C protective effect against DNA damage may be mediated by an increase in the detoxification of AOM, an alkylating agent that provokes DNA damage, resulting in antioxidant responses that confer protection within the colon.…”
Section: Discussionmentioning
confidence: 99%
“…I3C is a proagonist found in the Brassica family of vegetables. After ingestion, it undergoes condensation reactions within the acidic gastric environment resulting in several metabolites such as 3,3'-diindolylmethane (DIM) and indolo [3,2-b]carbazole (ICZ), both of which have high affinity for AHR [34]. Although the chemopreventive effect of I3C has been recognized before, this is the first study to establish that the I3C protective effect within the colon is dependent on AHR.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants are rich sources of important metabolites, which are potential sources of antioxidant, antimicrobial, anti-inflammatory, and anticancer activities (Hernandez et al, 2000; Polya, 2003; Maruthanila et al, 2014). The utilization of herbal medicine in treating infectious diseases have been practiced for 1000s of years and will continue to provide mankind with new remedies (Cragg and Newman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Both I3C and DIM have been reported to possess potent anticancer activity through its ability to regulate cancer cell cycle, induction of apoptosis and major oncogenic signaling pathways (144). In colon and pancreatic cancer cell lines, DIM treatment leads to induction in the expression of miR-146a thereby targeting EGFR, IRAK1 and NFkB mRNAs (145).…”
Section: Mirnas and Essential Nutritional Factorsmentioning
confidence: 99%